2022
DOI: 10.3389/fonc.2021.817220
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Patient Selection for Irreversible Electroporation of Locally Advanced Pancreatic Cancer: Analyses of Survival

Abstract: BackgroundIrreversible electroporation (IRE) has emerged as a viable consolidative therapy after induction chemotherapy, in which this combination has improved overall survival of locally advanced pancreatic cancer (LAPC). Optimal timing and patient selection for irreversible electroporation remains a clinically unmet need. The aim of this study was to investigate preoperative factors that may assist in predicting progression-free and overall survival following IRE.MethodsA multi-institutional, prospectively m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…7 Specific to PC, the acellular structural components of blood vessels are not damaged by IRE, 8 which permits safe treatment of tumors with vascular involvement. Multiple individual institutions [9][10][11] and a few multicenter studies [12][13][14][15] have published clinical experiences with IRE for locally advanced PC. These nonrandomized studies suggest that IRE is associated with longer survival than standard therapy alone.…”
Section: What This Study Addsmentioning
confidence: 99%
“…7 Specific to PC, the acellular structural components of blood vessels are not damaged by IRE, 8 which permits safe treatment of tumors with vascular involvement. Multiple individual institutions [9][10][11] and a few multicenter studies [12][13][14][15] have published clinical experiences with IRE for locally advanced PC. These nonrandomized studies suggest that IRE is associated with longer survival than standard therapy alone.…”
Section: What This Study Addsmentioning
confidence: 99%
“…To optimize the patient criteria for IRE, a recent multi-institutional study concluded that patients with normal Carbohydrate Antigen 19-9 levels before surgery and avoiding radiation therapy before IRE, in addition to administering FOLFIRINOX plus GEM or abraxane induction chemotherapy, are good interpreters of better survival rate after IRE [ 196 ]. Moreover, IRE is contraindicated with cardiac arrhythmia pacemakers [ 179 ].…”
Section: Locoregional Therapiesmentioning
confidence: 99%
“…Patient selection for IRE is essential. 23 , 24 , 25 Narayanan proposed that patients should be reviewed in a multidisciplinary tumour board to determine if they are suitable candidates for IRE. 23 Some proposed criteria include having an Eastern Cooperative Oncology Group (ECOG) status of 0–1, with Stage 3 LAPC or low volume Stage 4 metastatic disease that has been stable over time.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that younger patients (60 years and below), patients without more than two comorbidities, and patients without diabetes display superior post-IRE outcomes. 24 On top of these, anatomic tumour characteristics need to be considered, with smaller tumours generally having prolonged survival outcomes. Vascular involvement of ≤180° of their affected structure is also more likely to have significantly longer overall survival.…”
Section: Introductionmentioning
confidence: 99%